Didactics as a factor of innovation in the educational process and in preparation for KROK 1 - general medical training - Belenichev, I. F.; Samura, I. B.; Bukhtiyarova, N. V.; Kuchkovskyi, O. M.; Bessarab, G. I.; Бєленічев, Ігор Федорович; Самура, Ірина Борисівна; Бухтіярова, Ніна Вікторівна; Кучковський, Олег Миколайович; Бессараб, Георгій Ігнатович (My University, 2022)
The modern system of higher medical education in Ukraine is characterized by rapid changes dictated by modern requirements, in particular its integration into the European educational space. The educational course Pharmacology is among the priority components in the system of higher medical education and plays a role an important link that combines theoretical and clinical discipline, knowledge of which ensures proper scientific and theoretical training of future physicians and allows them successfully use the opportunities of pharmacotherapy in their clinical practice.